COLLABORATORY COMMITMENT DERIVED FROM PROFESSIONALS’ EXPERIENCES WITH COOPERATION ACROSS SERVICE-LEVELS - Bachke, Carl Christian (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2022)
The services of the sectors of health and education have become more specialized. To prevent services from appearing fractured, professionals must work together and coordinate their help. This study deals with what professionals have experienced as positive for the collaboration. Seven informants, four from the municipal level and three from the specialist level, have been interviewed about what create collaborative commitment in their help to people affected with mental disability and mental disorders. The findings show that four factors inclusive their sub-attributes contribute positively: (1) The professionals are committed to prosocial attitudes, like respect, humility, openness, trust/confidence. (2) They prioritize user-focus which means that what benefits the user is number one to-do. (3) They commit themselves to certain dialogically prosocial communicative and relation-building actions, e.g., listening/audibleness, giving feedback and praise, advising, negotiate joint decisions. (4) They are stimulated by internal motivation like learning pleasure and increased understanding and reflection of knowledge combined with a job-arena characterized by facilitating human relationships, communication availability and mutual accommodation, and an encouraging, commendable, and facilitating management. These findings are consistent with what other collaborative research has pointed out as quality-enhancing. Based on the findings a theoretical model of collaboratory commitment is constructed.